"Magic Dirt": Transcending Great Divides in Scott McClanahan's Crapalachia - Eva-Maria Müller (Journal of the Austrian Association for American Studies)
Scott McClanahan, rising star of the US Indie Lit world and "Poet Laureate of Real America" (Moran), writes miasmic chronicles of life in a West Virginian holler. In Crapalachia: A Biography of Place (2013), as in many of the tales he releases in Dickensian pace, McClanahan ties the fate of a place to the fate of its people and connects environmental destruction to the ruins of life. Where mountains are stripped away, happiness is not at home. McClanahan tells family stories of deforestation and disability, mining disasters and mental illness, structural poverty and opportunities denied. His stories are about the slow and fast deaths of forgotten people in forgotten places and he tells them with a ballistic sensibility that opens up new spaces to negotiate difference. Crapalachia is a threnody for a wounded region that complicates imagined hierarchies of center and periphery and blends the worlds of fact and fiction as well as tragedy and comedy. The semi-autobiography mines so deeply for privation that, at its close, it lays bare some of the most hopeful principles of American transcendentalism. In between personal hardships, local misery, national movements, and universal human experience, McClanahan has us see "Crapalachia as the center of the world" (35). This paper explores how the aesthetic, narrative, and stylistic strategies of Crapalachia help navigate the local, national, and global routes of fictions of disregard.